Forest cover and topography regulate the thin, ephemeral snowpacks of the semiarid Southwest United States. Issue 4 (27th February 2020) - Broxton, Patrick D.; van Leeuwen, Willem J.D.; Biederman, Joel A.
Abstract: In the Southwest United States, water resources depend heavily on snowpacks, which are temporally and spatially limited in this warm, semiarid region. Snow accumulation and ablation in the Southwest are heavily influenced by forest structure. Therefore, water resource managers urgently need to understand the future impacts of unprecedented forest changes now occurring from drought, insect infestation, and forest management. Here, we present state‐of‐the‐art maps and time series of snow water equivalent (SWE), which account for spatial variability of snow depth and snow density over a large range of forest structure and topographies in the highlands of central Arizona. We show that the degree of forest cover and its geometry largely determine which areas have more/less snow accumulation and faster/slower ablation. Compared with under‐canopy areas, open areas can have 20–30% more accumulation and ablation rates can vary by 15–30% in sunny areas versus shaded areas. Although SWE response to forest cover is widely variable, depending on how much shading the trees provide versus how much snow is intercepted and lost through canopy sublimation, dense forests generally have less SWE than sparser forests. In general, SWE is optimized at intermediate levels of forest cover (~30–50%) on flat and north‐facing slopes. Somewhat counterintuitively, increasing forest cover generally causes a reduction of SWE on south‐facing slopes, where trees are less effective at reducing radiative forcing at the snow surface due to less efficient shading and increased enhancement of longwave radiation from the warm canopy.